A model-based strategy for developing sustainable cosmetics small and medium industries with system dynamics - Uly Amrina; Akhmad Hidayatno; Teuku Yuri M Zagloel (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Global customer consciousness for more sustainable products and government requirements for a more sustainable industry have motivated cosmetics small and medium industries (SMIs) to innovate the strategy by integrating sustainability principles into their manufacturing processes. However, the dynamic complexity of balancing sustainability efforts, stakeholders' interests, and uncertainty in material pricing require a conceptual reference model to help managers and decision-makers cope with the transition process. This work therefore proposes a model-based strategy using system dynamics to assist managers and stakeholders in SMIs to clarify their possible pathways and to offer a framework to understand, guide, and generate future strategies. In multiactor, multistakeholder conditions, the proposed methodology can provide insights into how stakeholders can effectively intervene to improve sustainability through open innovation dynamics models. The case study presented here on a personal care cosmetics company demonstrates several leverage points and obstacles, thereby allowing each stakeholder to understand their strategic role in realizing sustainable cosmetics SMIs.
Keywords: 650; sustainability; cosmetics; model-based strategy; open innovation dynamics; small and medium industries (SMIs); system dynamics (SD)